(3JChjd eTcd GdbQBf GdcQjes - (3YHO Gddg Hf eSde Hf bJjHI GdOjnfnhQqj, CHh eMeO, GHf obnJrjnHI, J (B276 (3g` s
(3ChdgG (B:s
(3bQC YdjfG CHh eMeO bGSe Hf CUHZ GdMeO ddg GdPi fgL dfG SHd GdQTGO s
(3BNQgG (B:s
(3BNQ eG jbQC efg bhdg (B: (3hYdi GdPjf gGOhG MQ efGcd Pi XaQ (B: (3Ci Pi eNdH ef GdWjQ hcd Pi MGaQ ef GdOhGH hcPdc bGd GdeaSQhf hSei GdMGaR XaQkG Ydi GdGSJYGQI s
(3GdfSNI HgG MhGTs
(3QhGjI CHh eMeO bGSe Hf CUHY GdCfOdSi J SfI (B340s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B137s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs